Pengaruh Keberadaan Marketplace Terhadap Minat Beli Konsumen pada Toko Konvensional di Kelurahan Gunung Terang Kota Bandar Lampung - Nina Lelawati; Ratmono Ratmono; Fitriani Fitriani (Akuisisi: Jurnal Akuntansi, 2021)
The existence of Shopee, Tokopedia, Lazada, Bukalapak, blibli.com and other marketplaces has more or less been realized by the entire community. This gives rise to the phenomenon of diminishing buying interest in Conventional Store customers who sell their products offline. The purpose of this study was to analyze the effect of the existence of a Marketplace which refers to the variables of price, product completeness, convenience, and promotion on the buying interest of conventional store customers in Gunung Terang Village, Bandar Lampung City. This study uses a sampling research method with accidental sampling technique with the number of respondents as many as 103 Conventional Store Customers in Gunung Terang Village. Data collection techniques using literature study, interviews, observations and questionnaires. Data management in this study will use the smartPLS software version 3.3. The results of the study found that the variable price and product completeness had a positive and significant effect on consumer buying interest, while the convenience and promotion variables had no effect on consumer buying interest in conventional stores